Seismotectonics of the Koryak Highland — one of active edge of the continent of Eurasia - G.P. Yarotskyy; A.V. Nazarevych; L.Ye. Nazarevych (Геофизический журнал, 2020)
In the article the features of the general seismotectonics of the Koryak Highland as the northwestern part of the framing of the Bering plate, including the latest (09.01.2020) seismic activation in the area of Mount Ledyanaya are presented. Comparison with the general seismotectonics of the Ukrainian Carpathians, another of the moderately active platform outskirts of the Eurasian continent is also given. These features are established on the basis of a complex of geological-geophysical and the latest GNSS data and a detailed system analysis of the structural elements of the geological-tectonic system and seismotectonic activity of the Koryak region and its discrete zones using seismic data from the catalogue of the Kamchatka Branch of the Geophysical Survey of the RAS. The researches methodology is based on the author’s geological and geophysical concepts of the block-key structure and tectonics of lithosphere of the active margins of the continents of the Pacific mobile belts of seismicity and volcanism and the «crocodile» alpine tectonics of the Ukrainian Carpathians. It is shown that the geomechanics of the Koryak region is a complex spatiotemporal combination of collision, shear and horst-graben («keyboard-like») tectonic processes, which reflect the general features and characteristic peculiarities of the geodynamics and seismotectonics of the Bering plate and the Koryak seismic belt as the northwestern part of its frame. Those processes appear in the peculiarities of the tectonic structure of the regions lithosphere and in the features of regional and local seismicity. In particular, for the first time by a complex of system data, the shear component of the movements of the Bering plate relative to the Eurasian plate was tracked in detail and the reflection of this component in the features of local seismotectonic processes was traced. According to seismicity monitoring data for the period 2000—2020 a tectonic-linked earthquake map of the Koryak seismic belt, extending along the northwestern coast of the Bering Sea, including the Koryak Highland, was constructed. By the strong seismic events and swarms of aftershocks in the belt the Ilpyrsky, Khailino, and Mount Ledyanaya high-magnitude (with M > 5.0) seismogenic centers have been identified. The connection of these seismogenic centers with the peculiarities of the tectonics of the region is traced. The collisional-rheological and deep-tectonic genesis of «keyboard-like» tectonics in the highlands and its relationship with high-magnitude seismogenic units and volcanogens of the Koryak-Chukchi Cenozoic volcanic belt are also traced. A comparative analysis of the seismotectonics of the Koryak Highland and the Ukrainian Carpathians made it possible to more clearly trace the general features and the peculiarities of the components of the «keyboard-like» and «crocodile» seismotectonics of these regions. The researches results make it possible to more reliably evaluate the level and characteristics of seismic hazard for the considered regions, especially for the Koryak Highland, and they should also be taken into account at minerals exploration here and at organizing the work of mining enterprises.